2023
DOI: 10.3389/fgene.2023.1089830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for donor-derived cell-free DNA quantification in plasma and urine from solid organ transplant recipients

Abstract: In allograft monitoring of solid organ transplant recipients, liquid biopsy has emerged as a novel approach using quantification of donor-derived cell-free DNA (dd-cfDNA) in plasma. Despite early clinical implementation and analytical validation of techniques, direct comparisons of dd-cfDNA quantification methods are lacking. Furthermore, data on dd-cfDNA in urine is scarce and high-throughput sequencing-based methods so far have not leveraged unique molecular identifiers (UMIs) for absolute dd-cfDNA quantific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…High coefficient of correlation with respect to the predicate centralised dd‐cfDNA assay has also been observed at end‐user level based on the results from a large kidney transplant cohort multi‐centre study (data not shown, submitted for publication). This kit assay has also been compared with alternative methods, such as short tandem repeat genotyping by quantitative fluorescence PCR (QF‐PCR), 17 droplet digital PCR, 39 and high‐throughput sequencing 40 using clinical samples. dd‐cfDNA results from these different methods showed mutual agreement with high coefficients of correlation, except agreement between QF‐PCR and NGS <5%, owing to limited sensitivity of QF‐PCR and greater sensitivity of NGS in this range 17 …”
Section: Discussionunclassified
“…High coefficient of correlation with respect to the predicate centralised dd‐cfDNA assay has also been observed at end‐user level based on the results from a large kidney transplant cohort multi‐centre study (data not shown, submitted for publication). This kit assay has also been compared with alternative methods, such as short tandem repeat genotyping by quantitative fluorescence PCR (QF‐PCR), 17 droplet digital PCR, 39 and high‐throughput sequencing 40 using clinical samples. dd‐cfDNA results from these different methods showed mutual agreement with high coefficients of correlation, except agreement between QF‐PCR and NGS <5%, owing to limited sensitivity of QF‐PCR and greater sensitivity of NGS in this range 17 …”
Section: Discussionunclassified
“…Strategies to differentiate between the two include using sex‐specific markers in cases where there is a donor–recipient sex mismatch, genetic differences between the donor and the recipient, including single‐nucleotide polymorphisms, amplification of HLA‐specific genes and copy number deletion polymorphisms and tissue‐specific methylation patterns in cfDNA (Gielis et al., 2015) (Figure 2b). Several methods can be used to quantify dd‐cfDNA, including real‐time quantitative PCR (RT‐qPCR), digital droplet PCR, organ‐specific methylation patterns, NGS, mass spectrometry and microarray analysis (Dengu, 2020; Goh et al., 2017; Kueng et al., 2023) (Figure 2c). Studies have shown that dd‐cfDNA can be a useful biomarker for rejection in solid organ transplantation, particularly in cases of acute cellular rejection (ACR) and AMR (Figure 2d).…”
Section: Main Textmentioning
confidence: 99%
“…After thawing the plasma at 4 • C, cfDNA was isolated with the QIAamp Circulating Nucleic Acid Kit (Qiagen, Hilden, Germany), according to the protocol provided by the manufacturer, as previously described [17].…”
Section: Cfdna Extractionmentioning
confidence: 99%
“…Urinary cfDNA was extracted from 15-50 mL of urine after thawing at room temperature (RT) either with the Quick-DNA Urine Kit (Zymo Research, Irvine, CA, USA) as previously described [17] or using a quaternary ammonium anion exchange resin-based Q Sepharose method based on the method published by Dudley et al [18].…”
Section: Cfdna Extractionmentioning
confidence: 99%